2013
DOI: 10.1111/iere.12034
|View full text |Cite
|
Sign up to set email alerts
|

The Welfare Gains of Age‐related Optimal Income Taxation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 32 publications
0
40
1
Order By: Relevance
“…By introducing separate tax schedules based on individual or household characteristics, governments could once more achieve distributional objectives at lower efficiency costs. Indeed, age-based taxation is shown to substantially improve the equity-efficiency trade-off in Weinzierl (2011);Bastani, Blomquist, and Micheletto (2013);and Fahri and Werning (2013). Similarly, Boskin andSheshinski (1983) andCremer Gahvari, andLozachmeur (2010) demonstrate that gender-based tax schedules can substantially improve equity, efficiency, or both.…”
Section: Tagging In Nonlinear Tax Schedulesmentioning
confidence: 95%
“…By introducing separate tax schedules based on individual or household characteristics, governments could once more achieve distributional objectives at lower efficiency costs. Indeed, age-based taxation is shown to substantially improve the equity-efficiency trade-off in Weinzierl (2011);Bastani, Blomquist, and Micheletto (2013);and Fahri and Werning (2013). Similarly, Boskin andSheshinski (1983) andCremer Gahvari, andLozachmeur (2010) demonstrate that gender-based tax schedules can substantially improve equity, efficiency, or both.…”
Section: Tagging In Nonlinear Tax Schedulesmentioning
confidence: 95%
“…Starting with Weinzierl (), many works in this literature, Farhi and Werning (), Bastani et al. (), Findeisen and Sachs (), and Stantcheva (), have shown that the bulk of the gains from using unrestricted instruments, that is, from attaining the constrained efficient allocations, is captured by the use of age‐dependent taxes. This mechanism design approach therefore offers an important reminder of how far one can get through the use of age‐dependent taxes and provides an important motivation for taking seriously these instruments.…”
Section: Introductionmentioning
confidence: 99%
“…6 Simulations of the discrete model have of course been presented earlier in the literature (see for instance Weinzierl 2011 andBastani et al 2013) but have usually been restricted to models with a small number of types and have not been used to characterize the overall shape of the optimal income tax schedule.…”
Section: Introductionmentioning
confidence: 99%